Three Dimensions of Patriotism: Heroic, Heroic-Civic, and Civic - Wilk, Sławomir (Roczniki Nauk Społecznych, 2026)
The aim of the study was to identify factors influencing the diversity of patriotic attitudes among: adult Poles aged 20+, secondary school students, and teachers. Types of patriotism (heroic, heroic-civic, and civic) and their relationships with various variables were analyzed. A nationwide representative survey was conducted in 2022. Data were collected using CAPI interviews (for teachers, N = 1,115, and adults aged 20+, N = 1,068) and CAWI surveys (for students, N = 3,718). The sampling procedure was based on a random selection from the Educational Information System database (for students and teachers) and the PESEL population register (for adults aged 20+), ensuring representativeness with respect to, among other factors, province, type of school, and selected socio-demographic characteristics. Heroic patriotism dominates among students, while adult Poles and teachers prefer a more diverse approach combining civic aspects. Higher levels of civic engagement, right-wing views, and positive attitudes towards faith correlate with patriotism.